Value of addition of coronary artery calcium to risk scores in the prediction of major cardiovascular events in patients with type 2 diabetes - Barak Zafrir (BMC, 2021)
Abstract Background The increased risk for cardiovascular events in diabetics is heterogeneous and contemporary clinical risk score calculators have limited predictive value. We therefore examined the additional value of coronary artery calcium score (CACS) in outcome prediction in type 2 diabetics without clinical coronary artery disease (CAD). Methods The study examined a population-based cohort of type 2 diabetics (n = 735) aged 55–74 years, recruited between 2006 and 2008. Patients had at least one additional risk factor and no history or symptoms of CAD. Risk assessment tools included Pooled Cohort Equations (PCE) and Multi-Ethnic Study of Atherosclerosis (MESA) 10-year risk score calculators and CACS. The occurrence of myocardial infarction (MI), stroke or cardiovascular death (MACE) was assessed over 10-years. Results Risk score calculators predicted MACE and MI and cardiovascular death individually but not stroke. Increasing levels of CACS predicted MACE and its components independently of clinical risk scores, glycated hemoglobin and other baseline variables: hazard ratio (95% confidence interval) 2.92 (1.06–7.86), 6.53 (2.47–17.29) and 8.3 (3.28–21) for CACS of 1–100, 101–300 and > 300 Agatston units respectively, compared to CACS = 0. Addition of CACS to PCE improved discrimination of MACE [AUC of PCE 0.615 (0.555–0.676) versus PCE + CACS 0.696 (0.642–0.749); p = 0.0024]. Coronary artery calcium was absent in 24% of the study population and was associated with very low event rates even in those with high estimated risk scores. Conclusions CACS in asymptomatic type 2 diabetics provides additional prognostic information beyond that obtained from clinical risk scores alone leading to better discrimination between risk categories.